Response surface optimization for a nonlinearly constrained irregular experimental design space. Issue 12 (2nd December 2019) - Ozdemir, Akin; Cho, Byung Rae
Abstract : Finding optimum conditions for process factors in an engineering optimization problem with response surface functions requires structured data collection using experimental design. When the experimental design space is constrained owing to external factors, its design space may form an asymmetrical and irregular shape and thus standard experimental design methods become ineffective. Computer-generated optimal designs, such as D -optimal designs, provide alternatives. While several iterative exchange algorithms for D -optimal designs are available for a linearly constrained irregular design space, it has not been clearly understood how D -optimal design points need to be generated when the design space is nonlinearly constrained and how response surface models are optimized. This article proposes an algorithm for generating the D -optimal design points that satisfy both feasibility and optimality conditions by using piecewise linear functions on the design space. The D -optimality-based response surface design models are proposed and optimization procedures are then analysed.